The Effect of Achievement Motivation and Competence on Athlete Achievement at the North Sumatra Student Sports Education and Training Center (PPLP) - Wahyu Hidayat; Uswatun Hasanah; Ihsan Azhari; Ahmad Fadlan (Yayasan Multidimensi Kreatif, 2025)
This study aims to analyze the motivation for achievement and competition for the achievement of athletes at the North Sumatra Student Sports Education and Training Center (PPLP). Where there are athletes' achievements. There are two independent variables, namely the number of athletes and the number of competitions. This study uses secondary data by conducting a data search through the North Sumatra Student Sports Education and Training Center (PPLP). The data analysis model in this study uses multiple linear regression. The results of the study showed that the variables of the number of athletes and the number of competitions had a significant effect on the achievement of athletes at the North Sumatra Student Sports Education and Training Center (PPLP).